Uso de equipamentos assistivos em centro de terapia intensiva : comunicação alternativa entre a equipe de cuidados de saúde e paciente - Palmeiras, Graciela de Brum (2013)
Communication is key in the relationship between people and can be performed by speech, writing or gestures. In certain situations oral communication may be impaired, unable writing and gestures cannot be interpreted clearly. That is the reality of patients unable to communicate orally admitted to the intensive care environment. Assuming that communication is a basic tool for the identification of nursing care and effective needs of patients qualifying assistance, this study aimed to evaluate the use of assistive equipment as an alternative method for communication between the health care team and patients admitted to the intensive care unit. The study is a quantitative and qualitative exploratory analytical and longitudinal nature. The study included 32 patients and 43 professional assistance team working on the unit. Were used in the statistical analysis the Mann-Whitney, Kruskal-Wallis and chi-square. We adopted a significance level of p ≤ 0.05. In this paper we present the results obtained with the use of the device. There were significant differences in the relationship between the condition of communication and patient sex (p < 0.001) and between home screens and gender interaction (p = 0.033). The communication provided by mobile assistive device can benefit both the construction of basic messages about the complex between patient and health professional. Already the results of the analysis of data from a qualitative and elaborate designs will be presented later. Will employ the method of content analysis and image. To address the meanings emerging research will be categorized into three classes: the patient's needs; communicative process with staff assistance; process inter-relationships with family members